Keberadaan Public Figure Dalam Akun Instagram Tempat Wisata: Studi Etnografi Virtual Keberadaan Public Figure Dalam Akun Instagram @lembang_parkzoo - Rachmaniar Rachmaniar; Renata Anisa (CV. Ulil Albab Corp, 2023)
Instagram has become a popular platform for promoting certain tourist attractions. Tourism managers also try to create interesting content on their Instagram accounts, one of which is by presenting public figures in their posts. @lembang_parkzoo is one of the tourist attraction accounts that features public figures in its Instagram posts. The Minister's wife and the Ustadz are present in the content on @lembang_parkzoo. This is certainly interesting to study regarding the presence of these public figures in this account. And to answer this question the author uses S-O-R theory, qualitative research methods, and a virtual ethnographic approach. The results found by the author were that the public figures in posts on the Instagram account @lembang_parkzoo were artists, animal lovers, preachers, and also athletes; Various comments are present in posts featuring public figures on the Instagram account @lembang_parkzoo, and this is in accordance with the S-O-R theory; Netizens have a certain pattern in posts featuring public figures on the Instagram account @lembang_parkzoo. This pattern always appears in every post that features public figures. This pattern includes netizens' desires to travel to Lembang Park Zoo, netizens' questions regarding Lembang Park Zoo, and the tendency of netizens to mention the names of other netizens' Instagram accounts - mentions in the comments column to invite them for travel to Lembang Park Zoo.